Manajemen Supervisi Kepala Sekolah Terhadap Profesionalisme Guru Di Sekolah Dasar - Puteriyani, Dina; Suriansyah, Ahmad; Harsono, Arta Mulya Budi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Quality education is one of the keys to developing superior human resources. One of the key elements in the education system is the quality of teachers and the role of the principal. Effective supervision management proves to be one of the roles that influence the quality of learning and teacher professionalism. This study aims to explore the collaborative supervision management of the principal towards teacher professionalism at SDN SN Sungai Miai 5 Banjarmasin. The approach used is descriptive qualitative with a case study design. Data were collected through technical triangulation, including interviews, observation, and documentation. The unit of analysis of the study is the supervision management process using a collaborative model towards teacher professionalism. The results show that the principal applies a collaborative supervision management model by involving teachers in every activity, building two-way communication, and encouraging deliberation in joint decision-making. Four themes were identified: (1) Supervisory Management (POAC), (2) Collaborative Model, (3) Impact, (4) Evaluation. This study concludes that collaborative supervision management is effective towards teacher professionalism and building a good school culture.